The New Approach of Using Image and Range Based Methods for Quality Control of Dimension Stone - Levytskyi Volodymyr (Reports on Geodesy and Geoinformatics, 2017)
The basis for the quality control of commodity dimension stone blocks for mining industry is the study of fracturing. The identification of fracturing in rock masses is one of the most important aspects in rock mass modelling. Traditional methods for determination properties of fracturing are difficult and hazardous. This paper describes a new approach of fracturing identification, based on image and range data, which realized by image processing and special software. In this article describes a method using new computer algorithms that allow for automated identification and calculation of fracturing parameters. Different digital filters for image processing and mathematical dependences are analyzed. The digital imaging technique has the potential for being used in real time applications. The purpose of this paper is the accurate and fast mapping of fracturing in some walls of the Bukinsky gabbro deposit.